2015
DOI: 10.1186/s12889-015-1776-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of adult Ethiopian patients enrolled in HIV care and treatment: a multi-clinic observational study

Abstract: BackgroundWe describe trends in characteristics and outcomes among adults initiating HIV care and treatment in Ethiopia from 2006-2011.MethodsWe conducted a retrospective longitudinal analysis of HIV-positive adults (≥15 years) enrolling at 56 Ethiopian health facilities from 2006–2011. We investigated trends over time in the proportion enrolling through provider-initiated counseling and testing (PITC), baseline CD4+ cell counts and WHO stage. Additionally, we assessed outcomes (recorded death, loss to follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 27 publications
10
51
3
Order By: Relevance
“…Table 1 presents the main characteristics and outcomes of reviewed studies[7–10,23,2830,39]. Studies were conducted from across Ethiopia and the majority of them were from the northern (4) and southern (3) part of the nation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the main characteristics and outcomes of reviewed studies[7–10,23,2830,39]. Studies were conducted from across Ethiopia and the majority of them were from the northern (4) and southern (3) part of the nation.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were analytical in type including: three case control studies[7,9,23], five retrospective cohort studies[8,10,29,30,39] and one prospective cohort study[28]. The majority of the studies (n = 7)[8–10,2830,39] assessed factors associated with LTFU and the remaining two studies[7,23] assessed defaulting. One study that assessed LTFU[28] also assessed ‘stopped treatment’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upward trends in the proportion of enrolments from the VCT were also documented in a prospective cohort analysis of adult patients in Tanzania [19], and in a multi-country retrospective data review of older HIV positive adults [20]. A recent retrospective study in Ethiopia however, reported an increase in the proportion of adults enrolling into care through PITC services over time [21]. However, this analysis was done at a time when PITC services were being scaled up in the country which may have biased the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Study limitations are inherent in the data source. We used routinely collected clinical data, which is more prone to errors, including missing information [21]. …”
Section: Discussionmentioning
confidence: 99%